3 albums met krantenknipsels van karikaturen door Behrendt, gemaakt voor het Algemeen Handelsblad - Behrendt, Fritz
3 albums met krantenknipsels van karikaturen door Behrendt, gemaakt voor het Algemeen Handelsblad.